"Rod–coil" copolymers get self-assembled in solution. (16th September 2019) - Xu, Fugui; Zhang, Jiacheng; Zhang, Pengfei; Luan, Xiangfeng; Mai, Yiyong
Abstract : This review paper describes the recent advances in solution self-assembly of amphiphilic rod-coil copolymers of various structures, which contain conjugated polymers, liquid crystalline polymers, polypeptides, or helical polymers as the rod blocks. Abstract : Supramolecular self-assembly of amphiphilic "rod–coil" copolymers in solution has attracted tremendous interest, as they exhibit distinct self-assembly behaviors profiting from the introduction of rigid segments, compared with coil–coil copolymers. The unique interplay between microphase separation of the rod and coil blocks with great geometric disparities leads to the formation of various ordered nanostructures including some unusual morphologies, such as ribbons, helices, nanosheets, and toroids, which are difficult to observe in the self-assembly of coil–coil copolymers. This article overviews the recent advances in tunable solution self-assembly of several common types of amphiphilic rod–coil copolymers, including block, alternating, graft, star, and hyperbranched/dendritic copolymers, which contain functional rod segments such as conjugated polymers, liquid crystalline polymers, polypeptides, and helical polymers. The discussions focus on the morphological control, distinctive optical/electronic properties, and stimuli-responsiveness of the assemblies, which make them potential functional materials particularly for optical, optoelectronic and biological applications.